The Playground Perception of Syrian Refugee Children - UYANIK, GÜLDEN (SPRINGER, 2022)
Drawings by children are key to understanding their experiences in various aspects such as perceptions of playgrounds and the events that happen in them. This study aims to reveal Syrian refugee children's perceptions of playgrounds. In the study, drawings of children who live in two different cities in Turkey were collated. The results showed that children draw slides, swings, and seesaws as playground tools, as well as trees, sun, clouds and flowers as natural materials. Additionally, children draw some human figures, other children, himself/herself, and adults (mother, father and teachers). Finally, it was interpreted that children also draw flags, houses, shelter, walls, and planes as other objects in their drawings about the playground. The children's drawings were influenced by their ages and genders, and the city's geographical structure, where they live and their family backgrounds. Besides, it is seen that children's social skills/development are reflected in children's drawings. Finally, it is seen that the play materials that children use in their drawings are the playground materials they use the most in daily life. While building playgrounds, the opinions of the children both refugees and locals, could be considered in order to support children's learning skills and imaginative world.
Keywords: Refugee children; Drawing; Playground; Perception; PLAY